Sound Governance: Optimalisasi Implementasi Program Tsunami Ready Community di Pemerintahan Daerah - Nadilati Fuddailah; Irhamna Atthahirrah Shadri; Afrijal (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2026)
Indonesia is one of the countries with the highest tsunami risk in the world due to its location along the Pacific Ring of Fire and active tectonic plate boundaries. To strengthen coastal community preparedness, UNESCO-IOC developed the Tsunami Ready Community (TRC) program as a global standard for community-based tsunami preparedness. However, the implementation of the TRC program in Indonesian local governments still faces various challenges, including limited institutional capacity, weak inter-agency coordination, low community participation, and the lack of optimal regulatory support and policy monitoring. This study aims to analyze the barriers to TRC implementation and examine the relevance of sound governance as an analytical framework for optimizing tsunami preparedness in Indonesian local governments. This study employs a descriptive qualitative approach using a library research method through a literature review of national and international journal articles, government regulations, and official reports from BMKG, BNPB, and UNESCO-IOC. Data were analyzed descriptively through data reduction, data presentation, and conclusion drawing. The findings indicate that TRC implementation in various regions still encounters problems related to institutional capacity, policy coordination, sustainability of community education programs, and preparedness evaluation systems. In this context, sound governance can be used as an analytical framework because it emphasizes transparency, accountability, participation, legal certainty, effectiveness, efficiency, and governmental responsiveness in disaster management policies. This study recommends strengthening the institutional capacity of BPBD, establishing formal inter-agency TRC coordination forums, integrating TRC indicators into regional development planning documents (RPJMD), developing community-based disaster education, and strengthening regulations and monitoring systems for tsunami preparedness implementation at the local level.